Curriculum guide for technology education for primary and secondary schools in the CARICOM - Gift, Edrick...[et al.] ([CARICOM Secretariat] [Georgetown]GY, 2000)
Contains a rationale which sets out the justification for the introduction of a programme in technology education. Enunciates a philosophy to underpin the programme and states goals and objectives. Provides a guide for the curriculum.